Influence of resolution in spatial and time for numerical modeling of levees - Dwornik, Maciej; Pięta, Anna (Geology, Geophysics and Environment, 2015)
Stability of geotechnical constructions, such as levees, is one of the most important issue for urban areas. The precise prediction of levees destruction during the flood can not only save human lives and properties, but also protect the natural environment. Water level changes and its influence on the stability of levee was conducted by 2D and 3D numerical modeling. The results of two dimensional numerical modeling shows that it can be regarded as a powerful and sufficient tool to estimate the stability of levees. The optimal size of grid and time step can make this calculation more efficient.